Inclusive education as a phenomenon of sociocultural reality of society - Кaбделовa, У. С. (Journal of Oriental Studies, 2018)
The article highlights the main ideas, principles and concepts of such international phenomenon as inclusive education. Successful implementation of the inclusive education model depends on many factors; key among them is the socio-cultural characteristics of the society. The article also discussed the introduction of foreign cases and their experience and features of implementation of inclusive education in different developed countries, such as Norway, the USA and South Korea.